2002
DOI: 10.1046/j.1532-5415.2002.50118.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Receipt of Hospice Care in Nursing Homes Improve the Management of Pain at the End of Life?

Abstract: Findings suggest that analgesic management of daily pain is better for nursing home residents enrolled in hospice than for those not enrolled in hospice.The prescribing practices portrayed by this study reveal that many dying nursing home residents in daily pain are receiving no analgesic treatment or are receiving analgesic treatment inconsistent with AMDA and other pain management guidelines. Improving the analgesic management of pain in nursing homes is essential if high-quality end-of-life care in nursing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
186
2
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 226 publications
(202 citation statements)
references
References 29 publications
11
186
2
3
Order By: Relevance
“…8,9 To identify residents who died with advanced dementia a diagnosis of ''Alzheimer's'' or ''Dementia other than Alzheimer's'' had to be documented on the MDS closest to death or on any Medicare Part-A claim (i.e., home health, hospice, hospital, outpatient, or SNF claim) in the last 12 months of life. The International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) diagnosis codes we used to capture dementia have been used by others 24,25 (290.xx, 291.2, 292.82, 294.1x, 294.8, 331.0-331.2, and 332.83).…”
Section: Data and Study Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9 To identify residents who died with advanced dementia a diagnosis of ''Alzheimer's'' or ''Dementia other than Alzheimer's'' had to be documented on the MDS closest to death or on any Medicare Part-A claim (i.e., home health, hospice, hospital, outpatient, or SNF claim) in the last 12 months of life. The International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) diagnosis codes we used to capture dementia have been used by others 24,25 (290.xx, 291.2, 292.82, 294.1x, 294.8, 331.0-331.2, and 332.83).…”
Section: Data and Study Populationmentioning
confidence: 99%
“…2-7 NH hospice care has been found to provide benefits to dying NH residents, including better pain management, 8 fewer hospitalizations, 9 and greater family satisfaction with end-of-life (EoL) care, [10][11][12] and the benefits of hospice have been shown to extend to residents with dementia. 8,9,13 Although the proportion of dying NH residents with advanced dementia accessing hospice almost tripled between 1999 and 2006 (to approximately 40%), 14 there remain important barriers to greater and timelier hospice access.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For patients, involvement of SPCS improve the "quality of dying" [55], pain assessment and management of people dying in nursing homes [43,44] and symptomatic manage-ment in people admitted to hospital [26] and meet needs [54] and satisfaction with care [9,28,30]. For caregivers, SPCS involvement has been found to improve satisfaction [28,54] and reduce anxiety [30].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that NH/SNFs are not meeting the resident or families' end-of-life care needs for comfort, pain relief and emotional and spiritual support 1,[6][7][8][9][10] . Hospice care in nursing homes has been associated with decreased hospitalizations, high quality pain management and a collaborative opportunity to provide palliative care to dying residents 11 .…”
Section: Introductionmentioning
confidence: 99%